How to make instrument writing skill rubric? - Yayan Sudrajat; Ni Wayan Ayu Permata Sari (Universitas Indraprasta PGRI, 2022)
Making rubrics needed on terminology of evaluation of Indonesian instructional, evaluation terminology which consists of tests, measurements, and assessments. To be able to make a measurable assessment in accordance with the skills to be achieved by the learner, it is necessary to have an assessment rubric. The purpose of making an assessment rubric is to make it easier for teachers to conduct assessments, while the purpose of this paper is to create an assessment rubric in measuring learners' language skills. The research method was carried out with descriptive qualitative methods using theoretical studies and rubric trials to several teachers who were involved. The result of this study are in the form of an assessment rubric that can be used by teachers in Indonesian subjects.Keywords: Evaluation; Rubric; Language Skills Rubric